Answer:
Explanation:
y = y₀ cos[tex]\sqrt{\frac{k}{m} }\times t[/tex]
a )
[tex]\frac{dy}{dt}[/tex] = - y₀ x [tex]\sqrt{\frac{k}{m} }[/tex] sin ( [tex]\sqrt{\frac{k}{m} }\times t[/tex] )
b ) If m = 4m
[tex]\frac{dy}{dt}[/tex] = - y [tex]\sqrt{\frac{k}{4m} }[/tex] sin ( [tex]\sqrt{\frac{k}{4m} }\times t[/tex] )
Magnitude of velocity will be decreased .
c )
[tex]\frac{dy}{dt}[/tex] = - y [tex]\sqrt{\frac{4k}{m} }[/tex] sin ( [tex]\sqrt{\frac{4k}{m} }\times t[/tex] )
magnitude of velocity will be increased .
d )
velocity = - y₀ [tex]\sqrt{\frac{k}{m} }[/tex] sin( [tex]\sqrt{\frac{k}{m} }\times t[/tex] )
= L [tex]\sqrt{\frac{ms^{-2}}{m} }[/tex] X 0
= L s⁻¹
= m /s
unit of velocity is consistent .